(untitled) (The Review of Diabetic Studies, 2025)
Background: High-dose intravenous vitamin C, often combined with thiamine (with or without hydrocortisone), has been proposed as “metabolic resuscitation” for septic shock, yet trial results remain discordant. This systematic review focuses on emergency department (ED)–admitted adults with septic shock and evaluates effects on 28-day mortality, organ dysfunction, and ICU length of stay (LOS). Methods: We conducted searches across PubMed, Embase, Cochrane CENTRAL, Web of Science, Scopus, and ClinicalTrials.gov (spanning January 2010–October 2025), with no linguistic restrictions imposed. Studies qualified for inclusion if they were randomized trials (RCTs) or comparison cohort designs recruiting adult participants (≥18 years) presenting with septic shock from emergency departments (or recruited within 24 hours of emergency presentation), evaluating elevated-dose intravenous ascorbic acid (≥1.5 g every 6 hours or 50 mg/kg every 6 hours) with or without thiamine (200 mg every 12 hours) against control/conventional treatment. The principal endpoint was mortality from any cause at day 28; additional endpoints encompassed SOFA score variation, days without vasopressor support, duration of ICU/hospital stay, and treatment-related complications. Methodological quality assessment (RoB 2/NOS) and GRADE frameworks were utilized. Results: Seven RCTs (n≈2,150) met criteria for qualitative synthesis; five informed quantitative mortality estimates. Pooled effects showed no reduction in 28-day mortality (e.g., RR 0.88, 95% CI 0.73–1.06). Vitamin C–based regimens were associated with modest improvement in organ dysfunction (ΔSOFA MD ≈ −0.6 within 72–96 h) and shorter vasopressor exposure ( 0.5–1 day), without consistent decreases in ICU LOS. Overall certainty was moderate for mortality and low–moderate for secondary outcomes; small-study effects were suggested. Conclusions: In unselected ED-admitted adults with septic shock, high-dose IV vitamin C—with or without thiamine—does not improve 28-day mortality despite modest physiologic benefits. Routine incorporation into early sepsis bundles is not supported. Future trials should prioritize ED-initiated dosing, biomarker-guided patient selection (ascorbate/thiamine deficiency), and standardized exposure.